Innovation Management and Organization Development in the Nigerian Banking System - Adebisi, S.A.; Babatunde, B.O. (My University, 2011)
Innovation management is a new concept that is given priority by all companies and countries nowadays. However, it took longer than expected for the developing countries, especially in Africa, to acknowledge the importance of innovation to the growth of a company and to the development of an economy. It has been argued that innovation is the engine room of all economies, and this has propelled the researcher to look at the importance of innovation by conducting a research study on “innovation management and organizational development”, using Guarantee Trust Bank and Unity Bank Plc. as case study. The researcher has selected and tested three research questions using the Pearson Product Moment Correlation Statistics and the t test statistics and the study revealed that for any organization to remain a market leader, such a company must be able to introduce innovation and effectively manage the changes that occur in their business environment. The findings have propelled the researcher to recommend that banking industries should maintain a continuous, effective R α D and allow its entire staff to act as agents of change by giving them a free hand to operate in an organization.
Keywords: innovation; management; development; modern technology; product movement correlation analysis